V-Neck Technique: A Novel Improvement to the Infra-Pubic Placement of an Inflatable Penile Implant. Issue 7 (22nd May 2017) - Shah, Bhavik B.; Baumgarten, Adam S.; Morgan, Kevin; Beilan, Jonathan A.; Bickell, Michael; Munarriz, Ricardo; Parker, Justin; Carrion, Rafael
Abstract: Background: Infra-pubic placement of an inflatable penile prosthesis (IPP) has a well-known configuration deformity from contralateral tubing that crosses the corporal bodies, resulting in tubing visibility and irritation under the penile skin. Aim: To present a novel step to eliminate this tubing crossover deformity. Methods: The V-neck technique was applied to five patients, two of whom underwent suprapubic fat pad excision with simultaneous infra-pubic IPP placement and three patients who underwent only infra-pubic IPP placement. The technique added an additional 1 minute of procedure time. The reservoir was placed on one (ipsilateral) side into the space of Retzius. Outcomes: Primary outcome measurements were esthetic appeal at follow-up, immediate postoperative complications, and difficulty of implementation of the technique. Results: The technique included the following steps. (i) The standard infra-pubic approach, as popularized by Perito (J Sex Med 2008;5:27–30), was used to place the reservoir and cylinders. The ipsilateral and contralateral cylinders and the reservoir were clamped and unconnected. (ii) Finger dissection was used to create a sub-phallic window and a U-shaped aortic clamp was used to pass the contralateral tubing. (iii) After passing the green tubing through the window, all connections were performed in the usual fashion. Tubing crossover was eliminated, as was passage of the right and left cylinder tubes down their respective gutters. Postoperative follow-up at 2 weeks showed no visible tubing. Clinical Implications: This simple maneuver could help prevent the discomfort of tubing crossover deformity commonly seen after infra-pubic placement of an IPP. Strengths and Limitations: This unique maneuver can be applied to all infra-pubically placed IPPs. Limitations include the small patient population and short follow-up. Whether this maneuver will make revision surgery more difficult is unclear. Conclusion: This technique is a novel step to infra-pubic IPP placement that adds minimal operative time and could eliminate visible tubing.